(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract Collaboration is the process of coming together and cooperating to address a challenging issue. The collaboration of the Philippine National Police and the Community is a powerful tool for fostering social stability and peace. The main goals of the police are to safeguard society, provide for the citizens’ freedom, justice, and security, and to prevent and deter criminal activity within society. Although it can be challenging for the police to effectively battle criminal activity in some complex cases, there are some situations in which they must work with the community to guarantee everyone is safe. Developed community relations for public cooperation and participatory leadership and socialization in the community. On the basis of such findings, recommendations were made that conduct regular joint meetings and planning sessions to discuss and address community safety concerns. This can help ensure that the police and barangay officials are aligned on their priorities and strategies.